2021
DOI: 10.21031/epod.860431
|View full text |Cite
|
Sign up to set email alerts
|

The Achievement Gap between Schools and Relationship between Achievement and Socioeconomic Status in Turkey

Abstract: Nowadays, the performances of education systems are monitored through national and international large-scale studies. In these studies, besides the academic performance of the countries, their status regarding equality in education is also considered. In large-scale studies the relationship between the socioeconomic status and academic achievement and the achievement gap between schools are emphasized. The achievement gap between schools is considered a chronic problem of Turkey, and socioeconomic differences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…However, it is crucial to acknowledge that multiple variables can influence this approach [2]. Previous research has identified several factors, such as learning pace, intelligence, self-esteem, personality traits, self-efficacy, motivation, study habits, parental attitudes, socio-economic status, and school type, that contribute to these academic outcomes [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…However, it is crucial to acknowledge that multiple variables can influence this approach [2]. Previous research has identified several factors, such as learning pace, intelligence, self-esteem, personality traits, self-efficacy, motivation, study habits, parental attitudes, socio-economic status, and school type, that contribute to these academic outcomes [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%